Variação da pressão intraocular no treinamento resistido realizado nas posições de decúbito dorsal e sentada, em pacientes com glaucoma - Soares, Alex Sander [UNIFESP] (2017)
Objective: To verify the variation of intraocular pressure (IOP) accomplished in two different positions, in sitting and supine position, on the leg press device in patients with primary open-angle glaucoma (POAG). Methods: Experimental research was carried out in a transversal way with six individuals, three males and three females between 50 and 70 years old. Three series of 15 movements were performed with a 60 second interval between the series, the IOP was measured at three moments, before the exercise (Pre), immediately after the third series (Post), and five minutes after the last series (5' Post). The volunteers performed two different protocols, situation 1 (S1): vertical leg press and situation 2 (S2): horizontal leg press. All volunteers performed the two training protocols randomly distributed at intervals of 72 hours between sessions. The control group (CG) was performed with the same volunteers being submitted to measurements at both positions S1 and S2, with IOP collected in the three situations. Results: In S1 there was a reduction of the IOP at the moment Post in relation to the Pre of the control group, and also there was a reduction compared to the same moment of the control group at the moment Post. In 5'Pós it occurred an even larger reduction compared to the Pre in the same intervention and of the Pre of the control group and in 5'Pós of the control group. In the S1 CG there was no significant reduction of the IOP, in the S2 the IOP significantly reduced in the moment Post in relation to the moment Pre of the same intervention, and had a decrease in 5Pós compared with the moment Pre of the same intervention, compared to the same moment 5'Pós of the GC S2. There was also a reduction, and in the same way there was a decrease of the 5'Pós with the Pre of the CG. Conclusion: There was a decrease in IOP of patients with primary POAG, due to resistance exercise and was not observes differential response of IOP of IOP according to the position of the exercise.